Effect of Preservative Solution Composition and Stalk Cut Angle in Maintaining the Shelf Life of Cut Flowers Chrysanthemum (Chrysanthemum morifolium R.) var. Kulo - Windi Lanni Timpalan; Beatrix Doodoh; Maria G. M. Polii; Jeanne M. Paulus; Meity R. Rantung; Annatje E. B. Inkiriwang (Sam Ratulangi University, 2023)
This study aims to examine the interaction between the composition of the preservative solution and the cut angle of the flower stalk in maintaining the shelf life of cut chrysanthemum flowers and to examine the effect of the composition of the preservative solution in maintaining the shelf life of cut chrysanthemum flowers and to examine the effect of the angle of cut flower stalks in maintaining the shelf life of cut chrysanthemum flowers. This research was conducted from January 2023 to February 2023 at the Genetics and Plant Breeding Laboratory. This study used a completely randomized design (CRD) factorial pattern with 2 factors, namely Factor A consisting of 3 levels with treatment A0: Water, A1: Sugar 25 g/L + Citric Acid 0.15 g/L + Bleach 1 mL /L, and A2: 25 g/L Sugar + 0.4 mL/L Vinegar + 1 mL/L Bleach and Factor B consists of 3 levels with treatment B1: Flat Cut (0Ëš), B2: Slanted Cut (30 Ëš), and B3: Bevel Cut (45Ëš). So that there were 9 treatment combinations and each treatment was repeated 3 times, so 27 experimental units were obtained. Each experimental unit has 2 samples, so that the total number of experimental units is 54 samples. Research data were analyzed using analysis of variance 2 factor ANOVA method with repetition and if it has an effect then it will be continued with the BNT test at the 5% level. The results showed that there was no interaction between the composition of the preservative solution and the cut angle of the flower stalks for all the observed variables. The composition of the preservative solution treatment A2: Sugar 25 g/L + Vinegar 0.4 mL/L + Bleach 1 mL/L had a single significant effect on maintaining the shelf life of cut flowers of chrysanthemum var. Kulo for 16.28 days. The cutting angle of the flower stalk had no significant effect on maintaining the shelf life of the cut chrysanthemum var. Kulo. Keywords: Preservative Solution, Cut Flowers, Chrysanthemum Abstrak Penelitian ini bertujuan untuk mengkaji interaksi antara komposisi larutan pengawet dengan sudut potong tangkai bunga dalam mempertahankan masa pajang bunga potong krisan dan mengkaji pengaruh komposisi larutan pengawet dalam mempertahankan masa pajang bunga potong krisan serta mengkaji pengaruh sudut potong tangkai bunga dalam mempertahankan masa pajang bunga potong krisan. Penelitian ini dilaksanakan pada bulan Januari 2023 sampai Februari 2023 di Laboratorium Genetika dan Pemuliaan Tanaman. Penelitian ini menggunakan metode Rancangan Acak Lengkap (RAL) pola faktorial dengan 2 faktor, yaitu Faktor A terdiri dari 3 taraf dengan perlakuan A0: Air, A1: Gula Pasir 25 g/L + Asam Sitrat 0,15 g/L + Pemutih 1 mL/L, dan A2: Gula Pasir 25 g/L + Cuka 0,4 mL/L + Pemutih 1 mL/L dan Faktor B terdiri dari 3 taraf dengan perlakuan B1: Potongan Datar (0Ëš), B2: Potongan Miring (30Ëš), dan B3: Potongan Miring (45Ëš). Sehingga terdapat 9 kombinasi perlakuan dan setiap perlakuan diulang sebanyak 3 kali, maka didapatkan 27 satuan percobaan. Setiap satuan percobaan terdapat 2 sampel, sehingga total keseluruhan satuan percobaan terdapat 54 sampel. Data penelitian dianalisis dengan menggunakan analisis ragam metode ANOVA 2 Faktor dengan pengulangan dan apabila berpengaruh maka akan dilanjutkan dengan uji BNT pada taraf 5%. Hasil penelitian menunjukkan tidak terdapat interaksi antara komposisi larutan pengawet dengan sudut potong tangkai bunga terhadap semua variabel pengamatan. Komposisi larutan pengawet perlakuan A2: Gula Pasir 25 g/L + Cuka 0,4 mL/L + Pemutih 1 mL/L berpengaruh nyata secara tunggal dalam mempertahankan masa pajang bunga potong krisan var. Kulo selama 16,28 hari. Sudut potong tangkai bunga tidak berpengaruh nyata dalam mempertahankan masa pajang bunga potong krisan var. Kulo. Kata Kunci: Larutan Pengawet, Bunga Potong, Krisan